KESALAHAN DALAM PENGUCAPAN OLEH KELAS TIGA MTS DARUL HIKMAH PEKANBARU DALAM MENGUCAPKAN KATA KATA BAHASA INGGRIS - Suci Lestari Raju; Fadly Azhar; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aim of this research was to find out the vowels that are difficult for the third year students of MTs Darul Hikmah Pekanbaru to pronounce and the sources of errors made by them. There were 251 population and only 22 students as the sample through cluster random sampling technique. The test was taken in audio recording. After analysing the data, it can be concluded that the most difficult vowel appeared in /ʌ/ (76.14%); while the easiest vowel was /ɔ/ (7.95%). In addition, the first source of pronunciation errors made by the students was Interlingual (31.82%) and the second source was Intralingual (18.18%).Key Words: Pronunciation, Errors, Analysis, and Students